2018
DOI: 10.1016/j.neurobiolaging.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Aging and a genetic KIBRA polymorphism interactively affect feedback- and observation-based probabilistic classification learning

Abstract: Probabilistic category learning involves complex interactions between the hippocampus and striatum that may depend on whether acquisition occurs via feedback or observation. Little is known about how healthy aging affects these processes. We tested whether age-related behavioral differences in probabilistic category learning from feedback or observation depend on a genetic factor known to influence individual differences in hippocampal function, the KIBRA gene (single nucleotide polymorphism rs17070145). Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…For KIBRA, animal studies have demonstrated that older C/C carriers express lower KIBRA protein, which negatively impacts hippocampal signaling pathways [26]. In humans, C/C carriers performed worse than T allele carriers in visuospatial learning [27,28], working and episodic memory tasks [29,30]. The ε4 allele of APOE has been found to be most strongly linked to risk for Alzheimer's disease (AD), but there is also evidence for a role of COMT, KIBRA and BDNF polymorphisms in AD development [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…For KIBRA, animal studies have demonstrated that older C/C carriers express lower KIBRA protein, which negatively impacts hippocampal signaling pathways [26]. In humans, C/C carriers performed worse than T allele carriers in visuospatial learning [27,28], working and episodic memory tasks [29,30]. The ε4 allele of APOE has been found to be most strongly linked to risk for Alzheimer's disease (AD), but there is also evidence for a role of COMT, KIBRA and BDNF polymorphisms in AD development [31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Here we found 28 factors that may represent perhaps the most important proteins that could mediate the age-controlling aspects of GPR19 biology. These proteins included multiple factors shown to exert a strong regulatory role in the aging process, e.g., DNA damage repair factors BLM [ 207 ], XRCC5 [ 208 ], RECQL4 [ 209 ], FAAP100 [ 210 ], FOXM1 [ 211 ], NUCKS1 [ 212 ], FEN1 [ 213 ]; energy metabolism factors UCP2 [ 214 ], PARP1 [ 215 ], HMOX1 [ 216 ], ARG2 [ 217 ], IDE [ 218 ]; cell cycle/fate control factors CDKN1A [ 219 ], CDK5 [ 220 ], WWC1 [ 221 ], CENPW [ 222 ]; transport and proteostasis regulation factors ZMPSTE24 [ 223 ], HSPA9, also known as Mortalin [ 224 ], SQSTM1 [ 225 ], PPM1L [ 226 ], PICALM [ 227 ]. To assess the degree of specificity of this cohort of GPR19-Aging-associated factors, we tested multiple (n = 10) random datasets the same numerical size as the unbiased aging dataset to assess the potential for random intersections between the GPR19-associated dataset with one the same size as the aging-specific dataset.…”
Section: Functional Gpr19 Molecular Signaturesmentioning
confidence: 99%
“…Indeed, one previous study found age-related effects of the DA receptor agonist bromocriptine on dedifferentiation in the HC (Abdulrahman, Fletcher, Bullmore, & Morcom, 2017). Moreover, HC-dependent episodic memory, spatial navigation, and learning have been found to be affected by genetic polymorphisms related to dopamine D2 receptor availability (COMT Val158Met, C957T CC; Papenberg et al, 2014;Li et al, 2013) or hippocampal function (KIBRA SNP rs17070145; Schuck et al, 2013Schuck et al, , 2018 in OA, but not YA. Based on these findings, we therefore also tested whether L-DOPA effects on walking direction decoding would be stronger in OA relative to YA.…”
Section: Introductionmentioning
confidence: 98%